Les chrétiens dans l’Orient : l’apport de l’histoire des religions à la coexistence religieuse en Méditerranée - Christian Lochon (Cahiers d’histoire.)
Today the Middle East is a space of religious violence where the dominating groups install, by law and by the power of social control, the monopoly of religious rites and dogmas. The finding is suprising for anybody who knows the history of the Mediterranean, history of conflicts, it is true, but finally also of permanent coexistence of groups of different religious believes. The article deals with different moments of this coexistence and shows, based on researches in the history of religion and in philology, the importance of successive loans and indeed the proximity of the three monotheistic religions which are today the very heart of the religious conflicts of our times.